Industry-specific specialization in venture capitalists' internationalization decisions - Antonia Nörthemann (Journal of Business Economics, 2022)
This study considers the impact of venture capitalists' industry specialization on cross-border investment decisions. The article argues that specialized venture capitalists' liability of foreignness is lower in specific international markets as assessments of the market and the behaviour of market participants are facilitated through industry-specific learning effects. Specialization leads to lower risk in cross-border investments from a venture capitalist's point of view. With increasing deal-specificity, the support and value enhancement of a foreign portfolio company are ensured in international markets due to the investor's specialization. A multilevel investigation of 46,525 worldwide venture capital deals from 2001 to 2019 in 69 countries shows a positive relationship between venture capitalists' industry specialization and internationality. The results show that the likelihood of a cross-border deal increases with higher levels of industry specialization. Furthermore, this effect is moderated by determinants at the institutional and portfolio company levels, reflecting the degree of information asymmetry between the venture capital firm and the portfolio company.
Keywords: G11; G24; M13; M16; O34; 650; Venture capital; Internationalization; Specialization; Industry experience; Learning